Preparing Christian health workers for international work: Evaluating a short global health course - Sneha Kirubakaran; Doug Shaw; Lawrie McArthur; Angus Miller; Anthony Radford (Health for All Nations, 2020)
Improving global health education to ensure health professionals are prepared and competent in the world's increasingly interconnected health-scape is a vital need. For many health professionals, global health education is facilitated through short, pre-departure courses in cross-cultural health and development work. There is currently limited literature on both the availability and the effectiveness of such courses. Our research aim was to explore the impact of a short course in global health education, designed and delivered by an Australian not-for-profit organisation, Intermed SA (Intermed). We conducted a short online survey of Intermed graduates, followed by semi-structured interviews with selected participants. The results indicate that Intermed's International Health and Development course was effective in achieving the course objectives as assessed by graduates, whilst also having a positive practical impact on the graduates' professional development.